Canonicity, setting, wisdom in the Deuterocanonicals : papers of the jubilee meeting of the International Conference on the Deuterocanonical Books - Xeravits, Géza G.; Zsengellér, József; Szabó, Xavér (Deuterocanonical and cognate literature studies ;, 2014)
The volume publishes papers read at the tenth International Conference on the Deuterocanonical Books, Budapest, 2013. The authors explore various aspects of this literature, with pre-eminent emphasis on their relation to diverse early Jewish texts and traditions; their reactions on Hellenism; and the way they treated as a canonical collection within their history of interpretation.